Trypanosomatid species inDidelphis albiventrisfrom urban forest fragments - Nantes, Wesley Arruda Gimenes; Santos, Filipe Martins; Macedo, Gabriel Carvalho de; Barreto, Wanessa Texeira Gomes; Goncalves, Luiz Ricardo [UNESP]; Rodrigues, Marina Silva; Chulli, Jenyfer Valesca Monteiro; Rucco, Andreza Castro; Assis, William de Oliveira; Porfirio, Grasiela Edith de Oliveira; Oliveira, Carina Elisei de; Xavier, Samanta Cristina das Chagas; et al. (Springer, 2020)
Urbanization results in loss of natural habitats and, consequently, reduction of richness and abundance of specialist to the detriment of generalist species. We hypothesized that a greater richness of trypanosomatid inDidelphis albiventriswould be found in fragments of urban forests in Campo Grande, Mato Grosso do Sul, Brazil, that presented a larger richness of small mammals. We used parasitological, molecular, and serological methods to detectTrypanosomaspp. infection inD. albiventris(n = 43) from forest fragments. PCR was performed with primers specific for 18S rDNA, 24S alpha rDNA, mini-chromosome satellites, and mini-exon genes. IFAT was used to detect anti-Trypanosoma cruziIgG. All hemoculture was negative. We detected trypanosomatid DNA in blood of 35% of opossum. Two opossums were seropositive forT. cruzi. The trypanosomatid species number infectingD. albiventriswas higher in the areas with greater abundance, rather than richness of small mammals. We foundD. albiventrisparasitized byT. cruziin single and co-infections withLeishmaniaspp., recently described molecular operational taxonomic unit (MOTU) named DID, andTrypanosoma lainsoni. We concluded that (i) trypanosome richness may be determined by small mammal abundance, (ii)D. albiventrisconfirmed to be bio-accumulators of trypanosomatids, and (iii)T. lainsonidemonstrated a higher host range than described up to the present.
Keywords: Trypanosoma cruzi; Leishmania; Trypanosoma lainsoni; DID; Trypanosomatidae